The Effect of Health WarnÄ±ngs in CÄ±garette PackagÄ±ng on Repurchase IntentÄ±on: A Study on IndonesÄ±an Consumers - Laksmidewi, Dwinita; Jonatan, Leonard Surijadi (APMBA (Asia Pacific Management and Business Application), 2016)
This study aims to examine the effect of health warnings on cigarette packs which are mortality-themed on repurchase intention, based on the perspective of terror management theory. This study used an experimental method with Indonesian adult smokers as participants. The results indicate that mortality warnings on cigarette packs conveyed in the form of pictures are more effective to influence the perception of health risks, compared to text warnings. The picture of deadly diseases caused by smoking ismore effective than the pictures do not show the deadly disease. Perceived health risk significantly mediates the effect of mortality warning on cigarette repurchase intention. However, smoking self-esteem does not significantly moderate the effect.